Comparative study of different cocoa (Theobroma cacao L.) clones in terms of their phytoprostanes and phytofurans contents. (15th May 2019) - León-Perez, Daniel; Medina, Sonia; Londoño-Londoño, Julián; Cano-Lamadrid, Marina; Carbonell-Barrachina, Ángel; Durand, Thierry; Guy, Alexandre; Oger, Camille; Galano, Jean-Marie; Ferreres, Federico; Jiménez-Cartagena, Claudio; Restrepo-Osorno, José; et al.
Highlights: First report of the occurrence of phytoprostanes and phytofurans in cocoa beans. The profiles of phytoprostanes and phytofurans varied according to the clone. Content of PUFAs were related to the amounts of phytoprostanes and phytofurans. Abstract: Cocoa has been widely discussed as a bioactive food rich in sensory stimulation and health benefits. However, no information has been provided concerning phytoprostanes (PhytoPs) and phytofurans (PhytoFs) in cocoa. These compounds are of interest because they play a role in the regulation of immune function. The present study included 31 cocoa clones. The PhytoPs and PhytoFs were quantified by UHPLC-QqQ-MS/MS. The total PhytoPs and PhytoFs contents ranged from 221.46 to 1589.83 ng g −1 and from 1.18 to 13.13 ng g −1, respectively. The profiles of the PhytoPs and PhytoFs identified in the cocoa beans showed significant differences among the clones analysed. The results indicate that dry fermented cocoa beans are rich in PhytoPs and PhytoFs, which may represent an additional benefit of the consumption of foods derived from cocoa.